Measuring the Environmental Costs of Carbon Emissions and Their Impact on the Market Values of Industrial Companies “A Comparative Study between Manufacturing and Listed Industrial Companies on the Amman Stock Exchange” - Halboosh, Ammar; Neama , Naama (The Gulf Economist, 2025)
study aims to measure the environmental costs of carbon emissions and their impact on the market value of industrial companies in Jordan, with a specific comparative focus between industrial companies listed on the Amman Stock Exchange (ASE) and non-listed manufacturing firms. The study employed a quantitative, longitudinal panel data analysis approach over a five-year period (2019-2023), including a sample of 22 listed companies and 30 non-listed manufacturing firms. The results revealed that the environmental costs of carbon (measured by using a Shadow Carbon Price) have a significant negative impact on the market values (measured by Tobin's Q) of the listed companies, while this impact was not statistically significant for non-listed firms. The study also found that this negative effect was strongest in high-emission sectors like energy and mining, and that corporate profitability (ROA) plays a mitigating role for listed companies.